2022
DOI: 10.1021/acs.analchem.1c05174
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Microfluidic Chip-Based Universal Fully Integrated Nanoelectronic System with Point-of-Care Raw Sweat, Tears, or Saliva Glucose Monitoring for Potential Noninvasive Glucose Management

Abstract: By combining the distinctive noninvasive feature with the peculiar complete functional implementation trait, fully integrated raw noninvasive biofluid glucose biosensors offer active and remote glucose monitoring while posing minimal harm or infection risks compared to the traditional invasive manner. However, each previously reported fully integrated raw noninvasive biofluid glucose biosensor is solely focused on single-type raw noninvasive biofluid analysis. Given the diversity and complexity of subjects' ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 58 publications
0
39
0
1
Order By: Relevance
“…Wearable colorimetric [17][18][19] and fluorescent [20][21][22] sweat sensors have offered visual sensing access via observation of color/absorbance/fluorescence depth related to the chromogenic/luminous reaction between indicator and analytes. Electrochemical sensors are widely adopted for sweat analysis by transducing target contents into currents or potential signals at miniature and specific electrode surfaces [23][24][25][26][27][28] . Electrochemical techniques are featured with high sensitivity and selectivity, where the electrodes can also be flexibly designed into different shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable colorimetric [17][18][19] and fluorescent [20][21][22] sweat sensors have offered visual sensing access via observation of color/absorbance/fluorescence depth related to the chromogenic/luminous reaction between indicator and analytes. Electrochemical sensors are widely adopted for sweat analysis by transducing target contents into currents or potential signals at miniature and specific electrode surfaces [23][24][25][26][27][28] . Electrochemical techniques are featured with high sensitivity and selectivity, where the electrodes can also be flexibly designed into different shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients, glucose levels in other biofluids (such as urine, saliva, tears, breath sweat, and interstitial fluids) and blood are correlated to some degree. Moreover, their ease of production and collection have led to extensive research and development on biofluid-based glucose sensors, making the glucose level detection and monitoring process more patient-friendly [ 42 ].…”
Section: Recent Developments In Various Biological Fluid-based Glucos...mentioning
confidence: 99%
“…Sun et al . [68] demonstrated a fully integrated point‐of‐care system with the capability to noninvasively monitor glucose concentration in various biofluids such as sweat, tears, and saliva glucose by combining a flexible and disposable microfluidic enzymatic biosensor.…”
Section: Noninvasive Chemical Sensors and Biosensorsmentioning
confidence: 99%
“…When sweat concentration was compared with a commercial blood-glucose system, it showed a good blood-sweat glucose correlation in healthy subjects. Sun et al [68] demonstrated a fully integrated point-of-care system with the capability to noninvasively monitor glucose concentration in various biofluids such as sweat, tears, and saliva glucose by combining a flexible and disposable microfluidic enzymatic biosensor.…”
Section: Sweat Biosensorsmentioning
confidence: 99%